Royal Free Hospital Nutrition Prioritizing Tools (RFH-NPT): Predictor of Malnutrition Risk among Chronic Liver Disease Patients - Rajab, Norashimah; Abdul Hamid, Syahrul Bariah (Jurnal Gizi dan Pangan, 2024)
This study is aimed to investigate the prevalence of malnutrition using Royal Free Hospital Nutrition Prioritizing Tools (RFH-NPT) and the correlation between malnutrition and RFH-NPT with clinical parameters. A total of 80 cirrhosis liver patients without liver cancer were enrolled in this prospective study. This study was conducted at Selayang hospital, which is the national tertiary referral centre for liver disease in Malaysia. We administered the nutrition screening of RFH-NPT to the patients within 24 hours after admission. The utilization of the RFH-NPT resulted in a higher incidence of nutritional risk, at 73%. The RFH-NPT revealed a higher proportion of Child Pugh C patients at risk for malnutrition (46/50 or 92%, p= 0.002) and had superior capability in identifying patients with intermediate and high risk for malnutrition (35/61 or 57.3%, p=0.012) within the subset of patients with Model for End- Stage Liver Disease (MELD) scores below 15. Hence, we propose that the utilization of the RFH-NPT enhances medical professional’s capacity for early-stage prediction of malnutrition risk in patients with cirrhosis predominantly attributed to hepatitis virus infection.